Lactate as a metabolite from probiotic Lactobacilli mitigates ethanol-induced gastric mucosal injury: an in vivo study - Yingpeng Huang; Jiali Zhang; Renjie Dong; Xiawei Ji; Yusha Jiang; Jianke Cen; Zhihuai Bai; Kairui Hong; Huihui Li; Jiajing Chen; Jinhui Zhou; Fanyu Qian; et al. (BMC, 2021)
Abstract Background Pre-administration of probiotic Lactobacilli attenuates ethanol-induced gastric mucosal injury (GMI). The underpinning mechanisms remain to be elucidated. We speculated that lactate, the main metabolite of Lactobacillus that can be safely used as a common food additive, mediated the gastroprotective effect. This study aimed to gain experimental evidence to support our hypothesis and to shed lights on its underlying mechanisms. Methods Lactate was orally administrated to mice at different doses 30 min prior to the induction of GMI. Gastric tissue samples were collected and underwent histopathological and immunohistochemical assessments, enzyme-linked immunosorbent assay, quantitative polymerase chain reaction (qPCR) and western blot analyses. Results Pretreatment with lactate at 1-3 g/kg significantly curtailed the severity of ethanol-induced GMI, as shown by morphological and histopathological examinations of gastric tissue samples. Significantly lower level of cytokines indicative of local inflammation were found in mice receiving lactate treatment prior to ethanol administration. Western-blot, immunohistochemical analysis and qPCR suggested that gastroprotective properties of lactate were mediated by its modulatory effects on the expression of the apoptosis regulator gene Bax, the apoptotic executive protein gene Casp3, and genes critical for gastric mucosal integrity, including those encoding tight junction proteins Occludin, Claudin-1, Claudin-5, and that for lactate receptor GPR81. Conclusion Lactate mitigates ethanol-induced GMI by curtailing local gastric inflammatory response, down-regulating the expression of the apoptosis regulator and executor genes Bax and Casp3, and up-regulating the expression of genes encoding tight junction proteins Occludin, Claudin-1, and Claudin-5 and the lactate receptor GPR81.